2016
DOI: 10.3168/jds.2015-9629
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental relationships of different measures of individual cheese yield and curd nutrients recovery with coagulation properties of bovine milk

Abstract: The aim of this study was to elucidate the relationships between various cheesemaking-related traits, namely the well-known traditional milk coagulation properties (MCP), the new curd firming and syneresis traits, the cheese yield, and the curd nutrient recoveries or whey losses (all measured at the individual level). Data were obtained from 1,167 Brown Swiss cows reared in 85 herds. A 2-L milk sample was collected once from each animal and assessed for 10 phenotypes related to changes in curd firmness (CF) ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…During the last 10 yr, several studies have estimated the genetic parameters of CMP, with data sets comprising from 892 to 17,577 reference measurements (Vallas et al, 2010;Cecchinato et al, 2011Cecchinato et al, , 2015Bittante et al, 2013;Poulsen et al, 2015) or 136,807 to 311,354 MIR predictions (Cecchinato et al, 2015;Bonfatti et al, 2017;Visentin et al, 2017). Using a micro-cheese-making procedure, some Italian studies reported low to moderate heritability for cheese yields (0.09 to 0.41; Bittante et al, 2013;Cecchinato et al, 2015;Cecchinato and Bittante, 2016;Bonfatti et al, 2017). In most other studies, coagulation properties were quantified with mechanical or optical lactodynamograph measurements after the addition of rennet.…”
Section: Introductionmentioning
confidence: 99%
“…During the last 10 yr, several studies have estimated the genetic parameters of CMP, with data sets comprising from 892 to 17,577 reference measurements (Vallas et al, 2010;Cecchinato et al, 2011Cecchinato et al, , 2015Bittante et al, 2013;Poulsen et al, 2015) or 136,807 to 311,354 MIR predictions (Cecchinato et al, 2015;Bonfatti et al, 2017;Visentin et al, 2017). Using a micro-cheese-making procedure, some Italian studies reported low to moderate heritability for cheese yields (0.09 to 0.41; Bittante et al, 2013;Cecchinato et al, 2015;Cecchinato and Bittante, 2016;Bonfatti et al, 2017). In most other studies, coagulation properties were quantified with mechanical or optical lactodynamograph measurements after the addition of rennet.…”
Section: Introductionmentioning
confidence: 99%
“…The main use of goat milk is in cheese making (Boyazoglu and Morand-Fehr, 2001); milk fat and protein, in particular casein, are the major contributors to cheese yield and they also affect milk coagulation properties (Cecchinato and Bittante, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of GWAS, quite often each trait is analyzed separately from each other. However, in the case of complex traits (e.g., CY), a plethora of different and possibly correlated components might be involved (Cecchinato and Bittante, 2016). Simulation studies found that integration of (correlated) phenotypes into a multivariate GWAS model might lead to an increased power for detecting causal loci compared with the classical univariate analysis (Galesloot et al, 2014).…”
Section: Introductionmentioning
confidence: 99%